The Modern Reproduction of a Mongol Era Bow Based on Historical Facts and Ancient Technology Research - Jason Wayne Beever (EXARC, 2017)
This bow was a concept, commissioned from Ulrich Velthuysen, a Swedish archer. This horn bow could be classified as a post-conquest design from early 14th century AD Mongolia. In this article, I will describe, step-by-step, the gathering and processing of materials, and the construction of this design of horn bow. Unfortunately, there are only a few pictorial representations of what bows may have looked like during 14th century AD Mongolia; although, there are many other variations of bows during this time period with similar characteristics. Bow styles varied from bowyer to bowyer, so while bowyers duplicated basic fundamentals of construction, there were many different methods of construction, and individual styles of bow-shaping. This article also aims to provide a historical background to a modern 2016 reproduction of a composite horn bow dating from the period of the Mongol expansion. The overview of the bow design includes all types of available and valid sources that speak in favour of its construction and other historical solutions these construction decisions were based upon.